The Effect Of Customer Experience On Lazada’s Customer Loyalty Through Trust As Intervening Variable - Kadarisman, Razes; Syahputra, Syahputra (eProceedings of Management, 2024)
Lazada is one of the international e-commerce companies that provides a convenient shopping experience. The purpose of this study is to analyze the effect of customer experience on the loyalty of Lazada users in Indonesia, with trust as the mediator. This study uses quantitative descriptive methods and path analysis, with a focus on the relationship between customer experience and trust among Lazada users. A sample of 200 respondents was included in the study, and the sample method was purposive nonprobability. The significance value of the customer experience on trust was 0.000 < 0.05. Therefore, the significance value of the influence on loyalty was 0.001 = 0.05. The sig value of the relation between customer experience and loyalty was 0.000, thus the conclusion of the study is positive and significant. Lazada customer trust is an indirect influence on the loyalty of customers. Therefore, trust is an intervening variable that influences the relationship between experience and loyalty. Keywords-customer experience,trust,customer loyalty